Effects of non-welded multi-rib stiffeners on the performance of steel plate shear walls. (May 2018) - Yu, Jin-Guang; Feng, Xiao-Tian; Li, Bo; Chen, Yung-Tsang
Abstract: This paper presents a numerical investigation of the dynamic performance of steel plate shear walls (SPSWs) stiffened by non-welded multi-rib stiffeners. Multi-rib stiffeners are installed on both sides of the steel plate and connected by threaded bolts through the plate, rather than direct welding as conventionally being done. The influence of constraints between multi-rib stiffeners and steel plate on the performance of SPSWs is first examined by finite element analysis. Afterwards, a numerical model for SPSW structure is developed and validated by the test results. The dynamic performance of SPSW structures with and without non-welded stiffeners is compared in terms of inter-story drift, acceleration response and out-of-plane deformation. Test results indicate that constraints between multi-rib stiffeners and steel plate slightly affect the loading capacity of SPSWs. The loading capacity of the SPSWs with non-welded multi-rib stiffeners is 5.8% lower than that with welded stiffeners. However, buckling of stiffeners can be avoided in the non-welded multi-rib stiffened SPSWs. For the dynamic performance of SPSW structures, use of non-welded multi-rib stiffeners is effective in reducing the inter-story drift, acceleration and out-of-plane deformation of SPSW structures under earthquake attacks, particularly for those subjected to main shocks followed with aftershocks. The use of non-welded stiffeners decreases the maximum inter-story drift and the maximum out-of-plane deformation of SPSW structures by 14.7% and 57.0%, respectively. In addition, non-welded multi-rib stiffeners can uniformly distribute the stiffness of SPSWs along the floors. In general, the proposed non-welded multi-rib stiffeners are effective in enhancing the dynamic performance of SPSWs. Highlights: Non-welded multi-rib stiffeners are proposed for steel plate shear walls (SPSWs). Finite element model for SPSW structure is developed and validated by test results. Use of non-welded stiffeners slightly reduces the loading capacity of SPSWs. Dynamic performance of SPSWs with non-welded multi-rib stiffeners is examined. Use of non-welded stiffeners enhances the dynamic performance of SPSW structure.